Pelatihan, Pendampingan, dan Respon Pelajar SMP Terhadap Kegiatan Komposting - Mulyati, Sri Slamet; Hidayah, Nurul; Hafiyana, Aliyah; Tryuwanasari, Feny; Firmansyah, Fahmi; Zakaria, Hafizh Muhammad (Jurnal SOLMA, 2023)
Background: Since the Covid-19 pandemic, existing environmental care activities have stopped at the junior high school. Previously, mushroom cultivation extracurricular activities had been carried out. Purpose: This service aims to measure the level of knowledge of students before and after counseling is carried out. Method: This community service activity involved students from SMP 1 Margaasih, Bandung Regency. The number of students involved was 60 people. Data collection was carried out by measuring the level of knowledge before and after counseling, and assessing students' responses to composting practices. Results: There is an increase in knowledge from the average value of 84.3 to 95.17. 3 Working Groups (Pokja) were formed to carry out composting to become compost. Stimulus production of finished compost packaging is made. Conclusion: the students who were given composting training and assistance were very enthusiastic and responded very well to the activity. Keywords : Response, students, training, mentoring, composting